Phytotechnologies with biomass production as a sustainable solution for military land revitalization - Pidlisnyuk, Valentina; Erickson, Larry; Stefanovska, Tatyana; Pidlisnyuk, Iryna; Davis, Lawrence (Fitotechnologia z produkcją biomasy jako zrównoważone rozwiązanie pozwalające na rewitalizację zanieczyszczonych terenów wojskowych, 2017)
The military sites polluted by heavy metals, oil and degraded organic products constantly pose health risks and negatively affect soil, water resources and biodiversity. The prospective approach for sustainable land management of these localities is a green technology based on phytoremediation combined with the production of biomass that allows to restore marginal land to the agricultural or urban land bank and to obtain profits from processed bioproducts. The main goal of this paper is to present the results on using the second generation biofuel crop Miscanthusxgiganteus for the revitalization of the former military sites in Ukraine, the Czech Republic and the US using such an approach. The results of laboratory experiments and two years’ field research proved the prospects of the phytotechnology and calls for further investigation related to economic value chain and behaviour aspects.
Biblioteka Regionalisty, 2017, Nr 17, s. 87-94
Keywords: contaminated military sites; miscanthus; biomass production; proved phytotechnology; behavior economics; zanieczyszczone tereny wojskowe; niewykorzystane grunty; produkcja biomasy; ekonomiczna wartość; studia behawioralne